Glastonbury Abbey: Archaeological Investigations 1904-79 - Gilchrist, Roberta (Society of Antiquaries of London, 2015)
This is a comprehensive study of the archaeological archives and artefact collections of Glastonbury Abbey, together with a new geophysical survey of the site. It analyses thirty-six seasons of archaeological excavation directed by such iconic figures as Sir William St John Hope, Sir Charles Peers, Sir Alfred Clapham and Dr Courtenay Arthur Ralegh Radford, and reveals new insights into the abbey's origins and historical development. Previous interpretations are challenged and new evidence is presented for the Saxon and later medieval phases of the abbey, including an important complex of early glass-working furnaces, dated c 700. The study reveals, for the first time, archaeological evidence for the Norman and later medieval monastic ranges and the luxurious abbot's hall and court.